(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to heart disease in India almost one person dies every day. A technique should be developed to detect the heart disease to reduce the number of deaths which is handy and at the same time reliable also. In the health care sector, Machine Learning plays an important role in the health care Industry. This paper deals with exploring and investigating different Machine Learning Algorithms. Also, it deals with applying multiple Algorithms on Heart Disease Dataset. In this study, from UCI the Dataset is taken. Six models were trained and tested, which are Logistic Regression, Random Forest Classifier, XGBoost Classifier, Support Vector Machine Classifier, Artificial Neural Network Classifier, K Nearest Neighbors Classifier. The Machine Learning algorithm Random Forest Classifier has proven to be the most accurate and reliable algorithm and hence used in the proposed system.